UiTM advances global vision with strategic MoU with Cardiff University - UiTM, AAGBS (Arshad Ayub Graduate Business School (AAGBS), 2024)
A monumental step forward in ourjourney toward global recognition was achieved on 26 March 2024 with the signing of a Memorandum of Understanding (MoU) between UiTM and Cardiff University. This strategic collaboration represents a significant milestone in UiTM's aspiration to become a Globally Renowned University by 2025 (GRU2025). The MoU signing was facilitated by Prof. Dr. Norzanah Mat Nor from Arshad Ayub Graduate Business School (AAGBS), whose leadership and dedication played a vital role in bringing this international partnership to fruition. Through this collaboration, both institutions will explore opportunities in academic exchange, joint research, innovation, and knowledge sharing, opening new pathways for students and academics alike. This partnership with Cardiff University reflects UiTM's strong commitment to internationalisation and excellence in higher education, creating a platform for meaningful global engagement and future-ready learning experiences.